Fostering effective use of ICT in agricultural extension: participant responses to an inaugural technology stewardship training program in Trinidad. Issue 4 (7th August 2020) - Gow, Gordon; Chowdhury, Ataharul; Ramjattan, Jeet; Ganpat, Wayne
ABSTRACT: Purpose: This study sought to investigate agricultural extension practitioners' response to an in-service training program offered by the University of the West Indies intended to foster effective use of ICTs (information and communication technologies) through a technology stewardship approach. Design/Methodology/Approach: This study reports on participants responses to an in-service training course on technology stewardship. Data were collected using a pre-course survey, formal course evaluation, classroom observation, and semi-structured interviews with participants. Kirkpatrick's four-level evaluation model was used to structure analysis of the results. Findings: Findings from this study show high levels of receptivity to the technology stewardship training course, that learning objectives of the course are achievable when offered as an in-service training program, and that most participants indicated an intent to apply their learning in a post-course activity. Results from the study raise a number of considerations for future course design and institutional policy in order to better support technology stewardship in practice. Practical implications: Technology stewardship training shows promise as a leadership-oriented approach for expanding the effective use of ICTs among communities of practice for agricultural extension in the Caribbean and elsewhere. Theoretical implications: This study applies key principles of social learning theory from a communities of practice approach with theoretical implications for the design of in-service training related to ICT adoption and use for agricultural extension education and policy. Originality/value: This study reports on the first known application of the technology stewardship model from the communities of practice literature to agricultural extension in the Caribbean.